FORMATION OF CRITICAL AND CREATIVE THINKING IN FIRST GRADE STUDENTS - Utaeva I.B. (Scholar Express Journal, 2023)
This article is devoted to an important problem - the formation of critical and creative thinking in first graders. Methods and approaches that help develop these skills in children are considered. Particular attention is paid to stimulating their curiosity and active exploration of the world around them, developing critical thinking and the ability to reason. Also considered are methods for the development of creative thinking, such as open-ended tasks and a game form of learning. The article emphasizes the importance of the role of the family and the creation of a favorable environment in the classroom for the successful formation of these skills in first graders.
Keywords: formation; critical thinking; first graders